William H. Shriver papers - Shriver, William H., 1887-
Transcript of a letter (1863 June 29) written by Shriver's aunt, S. C. Shriver, to her sister, Elizabeth Shriver Myer, describing the arrival of Confederate troops led by Generals Fitzhugh Lee and Jeb Stuart at the Shriver home in Union Mills, Md., and the accommodations made for them there; reminiscences (undated) of William H. Shriver relating to the role of his father, T. Herbert Shriver, as Stuart's guide into Gettysburg, Pa., on the eve of battle and of the elder Shriver's return to the Gettysburg battlefield in 1909; account of an interview (1960) with William H. Shriver about his father; and carbon copy of a letter (1961 January 25) from Shriver to historian Bruce Catton pertaining to the Shriver family's Civil War experiences.
Typewritten transcripts.
Resident of Union Mills, Md.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Catton, Bruce, -- 1899-1978 -- Correspondence; Lee, Fitzhugh, -- 1835-1905.; Myer, Elizabeth Shriver -- Correspondence; Shriver family; Shriver, S. C. -- Correspondence; Shriver, T. Herbert; Stuart, Jeb, -- 1833-1864.; Confederate States of America. -- Army; Gettysburg Campaign, 1863.; Maryland -- History -- Civil War, 1861-1865.; Pennsylvania -- History -- Civil War, 1861-1865.; Union Mills (Md.); United States -- History -- Civil War, 1861-1865 -- Battlefields; United States -- History -- Civil War, 1861-1865 -- Personal narratives